RUMAH TANGGA DAN HAM: Studi atas Trend Kekerasan dalam Rumah Tangga di Provinsi Jambi - Maisah, Maisah (Sunan Kalijaga State Islamic University & The Asia Foundation, 2016)
All households desire a happy life in this world and the next. This is built through commitments, agreed between the partners to achieve physical and spiritual happiness based on traditions and Islamic teachings. Many challenges present themselves during the process and many become sources of conflict: economic disparity, differences of opinion, cheating on one’s partner, all cause domestic violence; this leads to the destruction of the commitments founded in happiness. These are all prevalent in the cases of domestic violence subject to this research: in the Merangin, Batanghari and Kota Jambi Regencies. This, in the face of Islam’s strict rules against violence, especially to women. Women have the same rights and obligations with men and should receive strong legal protect from the law, whether the central or local governments.